Upaya Guru dalam Menangani Anak Slow Learner di SD Negeri Cot Preh Aceh Besar - Putri Maharani; Bukhari Bukhari; Israwati Israwati (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
This study aims to reveal how the efforts of teachers in dealing with slow learner children at SD Negeri Cot Preh Aceh Besar. The approach used in this research is descriptive qualitative. The subjects in this study were the fourth and fifth-grade teachers of SD Negeri Cot Preh Aceh Besar. Information collection is done by using the method of perception and interviews. Furthermore, all information from perceptions and encounters is handled during the information inquiry stage, specifically information reduction, information display, and final withdrawal. The results of the research conducted at SD Negeri Cot Preh Aceh Besar showed that the efforts made by teachers in dealing with slow learner children were, first; to take an individual approach to children. Second; using a variety of learning methods to attract children's attention and interest. Third; collaborate with parents. Fourth; always motivate children. Fifth; to familiarize the Indonesian language with children. Sixth; conduct group approaches and provide advice.